ORGANIZATION OF GROUP WORK IN CLASSES IN GEOGRAPHICAL DISCIPLINES (Pedagogy of Higher and Secondary Education, 2009)
In article problems of the organization of group work on occupations from geographical disciplines are considered.
Keywords: group work; organization